2008
DOI: 10.1177/0305735607086047
|View full text |Cite
|
Sign up to set email alerts
|

Health-promoting behaviours in conservatoire students

Abstract: This study focuses on health-promoting behaviours in students from two conservatoires, the Royal Northern College of Music (RNCM, Manchester, UK; n =199) and the Royal College of Music (RCM, London, UK; n = 74). The research questions concern (a) the levels and types of health-promoting behaviours among performance students and (b) the association of health-promoting behaviours with emotional state, perceived general self-regulation and self-efficacy. To address these questions, the students were surveyed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
64
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(92 citation statements)
references
References 22 publications
25
64
0
3
Order By: Relevance
“…This finding is similar to that observed in Kreutz et al (2008Kreutz et al ( , 2009). Furthermore, health responsibility was positively correlated with physical activity and nutrition, which were also correlated with each other.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is similar to that observed in Kreutz et al (2008Kreutz et al ( , 2009). Furthermore, health responsibility was positively correlated with physical activity and nutrition, which were also correlated with each other.…”
Section: Discussionsupporting
confidence: 93%
“…Fortunately, South African music students report self-efficacy as the highest scores, similar to other studies that have found self-efficacy as among the most important predictors of university students' health-promoting behaviors (Hong et al, 2007;Kim, 2006;Kreutz et al, 2009;Von Ah et al, 2004). Most notably, the findings of this study support the assumption that music students' healthy behaviors are similar across different socio-cultural contexts.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In those studies (Walker et al, 1988;Unalan et al, 2007;Al Kandari et al, 2008;Kreutz et al, 2009;Ay et al, 2012), it is found that consciousness of health increases with age. The reason we found contradicting results with this study may be associated with the stress and responsibilities of the medical students with rising ages.…”
Section: Discussionmentioning
confidence: 95%
“…A pesar de esto, estudios como el de Rickert, Barrett y Ackermann (2015) ponen de manifiesto la importancia de una buena concienciación corporal y hábitos de estudio saludables en el alumnado de cualquier edad, en previsión de posteriores lesiones. Además, si se produce una concienciación física y psicológica adecuada desde el comienzo del aprendizaje, es probable que el alumnado que continúa con estudios superiores sea capaz de una mejor autorregulación emocional y física (Kreutz, Ginsborg, & Williamon, 2009). En el caso concreto de los métodos analizados en esta investigación, esta responsabilidad está completamente delegada al profesorado, el cual ha de asumir cómo incorporar y crear hábitos saludables en la educación musical instrumental del alumnado novel (Rickert et al, 2015).…”
Section: Parámetros Físicosunclassified